Close Ties in European Local Governance
XXIX, 427 p. 16 illus.
Keywords: This book develops and tests a typology of local state-society relations. To deliver such a comparative study on institutionalized relations between local government and societal actors at the municipal level in Europe, the book identifies and classifies country-specific patterns of these institutionalized governance networks. This work explores the diversity within these institutionalized networks, approaching it from a strong comparative perspective that is anchored on a new typology allowing a more robust analysis of the identifiable patterns. It is a study with appeal to scholars and students of local government, public administration and political science as well as to those pursuing this debate and implementing similar agendas as practitioners. Filipe Teles is Assistant Professor at the Department of Social, Political and Territorial Sciences at the University of Aveiro, Portugal. Adam Gendźwiłł is Assistant Professor of Political Science and Human Geography at the University of Warsaw, Poland. Cristina Stănus is Associate Professor of Political Science at the Lucian Blaga University of Sibiu, Romania. Hubert Heinelt is Emeritus Professor of Public Administration, Public Policy and Urban Research at the Institute for Political Science, Technische Universität Darmstadt, Germany.